ANALISIS PERAN MODAL KERJA DALAM MENINGKATKAN PROFITABILITAS PADA KOPERASI PEDAGANG PASAR - Wati, Yulitiawati (Balance : Jurnal Akuntansi dan Bisnis, 2019)
This study aims to determine how the role of working capital in increasing profitability in the Muaradua Gunung Putih Market Traders Cooperative in South OKU Regency. The data used are secondary data, financial statements for 2013-2017. This research uses quantitative data analysis using descriptive approach. The analysis used is the analysis of the profitability ratio of Return on Equity and Return On Investment. Based on the discussion of ratio analysis, the level of profitability of the Muaradua Gunung Putih Market Traders Cooperative in the South Oku Regency over the past five years has fluctuated. Overall the level of working capital in increasing profitability at Muaradua Gunung Putih Market traders cooperatives does not significantly influence the level of profitability, this is evident from the level of working capital that increases every year but the level of profitability (ROE and ROI) obtained by the Gunung Putih Muaradua Market Cooperative from in 2013 - 2017 has increased and decreased. From 2013 - 2015 it is said to be quite good because profitability has increased, but in 2016-2017 it has declined. This is due to ineffective working capital management so the profit / profitability obtained is less than optimal.